Calcium balance in children treated with diphosphonates. Issue 3 (March 1975) - Uttley, W S; Belton, N R; Syme, J; Sheppard, H
Abstract : Serial mineral balances have been obtained in 3 children undergoing therapy with EHDP (ethane-1-hydroxy-1, 1-diphosphonate) for diseases involving ectopic calcification. Although clinical outcome was not uniformly satisfactory, all cases showed an overall reduction in calcium balance. This was due to increased faecal excretion of calcium and was most marked after a long duration of therapy. Although these results conflict with reported experience in adults, they are in agreement with published observations of the effects of EHDP on calcium absorption in experimental animals.